Transformation and Organizational Resilience: PAI Strategies in Facing Global Challenges in the Digital Era - Asep Deny Firdaus; Iyad Suryadi; Helmawati; Saeful Anwar (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2026)
This study aims to analyze Islamic Religious Education (PAI) strategies in facing global challenges and infrastructure limitations at MIN 5 Cilacap. Utilizing a qualitative approach with a holistic single case study design. Data were collected through observation, in-depth interviews, and documentation studies, then analyzed using Miles, Huberman, and Saldana's interactive model. Findings reveal planning strategies based on Managerial Realism and digital content curation (gatekeeping) effectively balance limited budgets. Technology implementation successfully shifts the paradigm from verbalism to concrete visualization and creates joyful learning through evaluation gamification. The success of this digital transformation is supported by organizational resilience, transformational leadership, and peer tutoring. Physical facility limitations in border areas can be overcome through pedagogical adaptability and social capital (humanware), establishing technology as an epistemological bridge without losing the spiritual essence of Islamic education. Keywords: Transformation and Organizational Resiliences, Global Challenges, Digital Era Abstrak: Penelitian ini bertujuan menganalisis strategi Pendidikan Agama Islam (PAI) dalam menghadapi tantangan global dan keterbatasan infrastruktur di MIN 5 Cilacap. : Menggunakan pendekatan kualitatif dengan desain studi kasus tunggal holistik. Data dikumpulkan melalui observasi, wawancara mendalam, dan studi dokumentasi, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldana. Temuan menunjukkan strategi perencanaan berbasis Realisme Manajerial dan kurasi konten digital (gatekeeping) yang efektif menyeimbangkan anggaran terbatas. Implementasi teknologi berhasil menggeser paradigma verbalisme menuju visualisasi konkret dan menciptakan joyful learning melalui gamifikasi evaluasi. Keberhasilan transformasi digital ini ditopang oleh resiliensi organisasi, kepemimpinan transformasional, dan kolaborasi sejawat (peer tutoring). Keterbatasan fasilitas fisik di wilayah perbatasan dapat diatasi melalui adaptabilitas pedagogis dan modal sosial (humanware), menjadikan teknologi sebagai jembatan epistemologis tanpa menghilangkan esensi spiritualitas pendidikan Islam. Kata Kunci: Transformasi dan Resiliensi Organisasi, Tantangan Global, Era Digital